Vietnamese nurses' lived experiences of hospital isolation during covid-19: A qualitative study - Anh, Mai (Indonesian Journal of Health Services, 2025)
Background: Nurses are at heightened risk of COVID-19 exposure due to their close contact with infected patients. During the COVID-19 pandemic, many nurses in Vietnam were infected and required to undergo hospital-based isolation. Despite the critical role of nurses in pandemic response, limited evidence exists regarding their personal experiences during the isolation process. Objective: This study aimed to explore the lived experiences of Vietnamese nurses who were infected with COVID-19 and underwent hospital-based isolation. Methods: A qualitative study with a descriptive phenomenological approach was conducted using Colaizzi’s method of analysis. Seven registered nurses from a public hospital in Ho Chi Minh City, Vietnam, who had completed hospital isolation and tested negative for COVID-19 were recruited through purposive sampling. Data were collected through in-depth face-to-face interviews conducted between March and June 2022. Thematic analysis was used to identify key experiences and meanings. Results: Three major themes emerged from the analysis. Before isolation, nurses experienced emotional shock, fear of transmitting the infection to others, and perceived social stigma. During isolation, participants reported loneliness, worsening physical symptoms, reliance on spiritual coping, and limited professional support. After isolation, nurses described persistent physical fatigue, spiritual growth, and a renewed sense of empathy and professional advocacy. Peer support and spiritual practices were identified as important factors in strengthening emotional resilience. Conclusion: Hospital isolation among nurses infected with COVID-19 generates significant psychological and spiritual challenges in addition to physical illness. Comprehensive support strategies, including mental health services, spiritual care, reintegration planning, and equitable treatment of healthcare workers when they become patients, are necessary to improve well-being and strengthen preparedness for future health emergencies.